Flow induces barrier and glycocalyx-related genes and negative surface charge in a lab-on-a-chip human blood-brain barrier model. Issue 9 (September 2021) - Santa-Maria, Ana R; Walter, Fruzsina R; Figueiredo, Ricardo; Kincses, András; Vigh, Judit P; Heymans, Marjolein; Culot, Maxime; Winter, Peter; Gosselet, Fabien; Dér, András; Deli, Mária A
Microfluidic lab-on-a-chip (LOC) devices allow the study of blood-brain barrier (BBB) properties in dynamic conditions. We studied a BBB model, consisting of human endothelial cells derived from hematopoietic stem cells in co-culture with brain pericytes, in an LOC device to study fluid flow in the regulation of endothelial, BBB and glycocalyx-related genes and surface charge. The highly negatively charged endothelial surface glycocalyx functions as mechano-sensor detecting shear forces generated by blood flow on the luminal side of brain endothelial cells and contributes to the physical barrier of the BBB. Despite the importance of glycocalyx in the regulation of BBB permeability in physiological conditions and in diseases, the underlying mechanisms remained unclear. The MACE-seq gene expression profiling analysis showed differentially expressed endothelial, BBB and glycocalyx core protein genes after fluid flow, as well as enriched pathways for the extracellular matrix molecules. We observed increased barrier properties, a higher intensity glycocalyx staining and a more negative surface charge of human brain-like endothelial cells (BLECs) in dynamic conditions. Our work is the first study to provide data on BBB properties and glycocalyx of BLECs in an LOC device under dynamic conditions and confirms the importance of fluid flow for BBB culture models.